Injectable Peptide Decorated Functional Nanofibrous Hollow Microspheres to Direct Stem Cell Differentiation and Tissue Regeneration. (13th October 2014) - Zhang, Zhanpeng; Gupte, Melanie J.; Jin, Xiaobing; Ma, Peter X.
<x xml:space="preserve">Abstract</x> Injectable microspheres are attractive stem cell carriers for minimally invasive procedures. For tissue regeneration, the microspheres need to present the critical cues to properly direct stem cell differentiation. In natural extracellular matrix (ECM), growth factors (GFs) and collagen nanofibers provide critical chemical and physical cues. However, there have been no reported technologies that integrate synthetic nanofibers and GFs into injectable microspheres. In this study, functional nanofibrous hollow microspheres (FNF‐HMS), which can covalently bind GF‐mimicking peptides, are synthesized. Two different GF‐mimicking peptides, Transforming Growth Factor‐β1 mimicking peptide Cytomodulin (CM) and Bone Morphogenetic Protein‐2 mimicking peptide P24, are separately conjugated onto the FNF‐HMS to induce distinct differentiation pathways of rabbit bone marrow‐derived mesenchymal stem cells (BMSCs). While no existing biomaterials are reported to successfully deliver CM to induce chondrogenesis, the developed FNF‐HMS are shown to effectively present CM to BMSCs and successfully induced their chondrogenesis for cartilage formation in both in vitro and in vivo studies. In addition, P24 is conjugated onto the newly developed FNF‐HMS and is capable of retaining its bioactivity and inducing ectopic bone formation in nude mice. These results demonstrate that the novel FNF‐HMS can effectively deliver GF‐mimicking peptides to modulate stem cell fate and tissue regeneration.